Stress state analysis and tensile-shear fracture criterion in combined puncture and cutting of soft materials. (December 2019) - Triki, Ennouri; Gauvin, Chantal
Abstract: The mechanics of the combined puncture and cutting of protective materials by a pointed blade are studied theoretically and experimentally, by means of stress state analysis. Through analysis of the stresses occurring during the puncture cutting of a variety of neoprene and nitrile rubber membranes by pointed blades with different cutting-edge angles, a force state of pushing/shear-dependent loading is formulated and discussed. By considering this combined loading as an asymmetric fracture, two equations—for pushing force component and shear force component—are then derived from the stress intensity factors. From this stress analysis, a model based on fracture mechanics theory is developed to calculate the critical force involved in the puncture cutting of soft elastomeric membranes. Stress state analysis also shows that the puncture cutting of elastomeric membranes involves all three fracture Modes, I, II and III, which are highly dependent on the friction coefficient of the cutting edge, the cutting-edge angle and the material thickness. It is found that combining compressive and shear stresses leads to the failure of elastomer materials under tensile-shear fracture regimes. Based on this study, we propose a unified strength criterion to explain the stress state that occurs in the puncture cutting of elastomeric membranes by a pointed blade. This criterion can describe all puncture-cutting mechanisms for materials undergoing a combination of compressive stress and shear stress. It can therefore be applied to a variety of soft materials punctured by pointed blades with cutting edges of different angles. Graphical abstract: Unlabelled Image Highlights: Stress analysis of combined puncture cutting of soft membranes by pointed blades. Pushing force and shear force are derived from the stress intensity factors. Pushing force and shear force generate the critical puncture-cutting force ( F P/C ). Combining compressive and shear stresses leads to the failure of materials. A unified strength criterion developed in the puncture cutting by a pointed blade.